Implementation of the Eye-tracking Methodology for the Evaluation and Analysis of Products in Retail Environments - Márquez, Brian Mauricio
Over time, different authors have coined the concept of neuromarketing (Bautista y Velásquez, 2018; Cenizo, 2022) as a discipline that studies brain processes which explain decision-making behaviors when choosing a good or service. In this sense, big brands are interested in knowing the consumer, which has led to multiple technological advances such as the eye-tracking methodology, seeking to study the visual behavior of the consumer with metrics that are associated with behavior. unconscious of the individual that manifests itself in brain activities. Methodology that can be used from different areas. This study will show the implementation of the eye-tracking methodology for the evaluation and analysis of products in the household cleaning category in MERCAVA retail, located in Pradera, Valle del Cauca (Colombia), a company interested in improving its allocation processes. It is intended that this article be used as a training tool for Marketing students, both at the Centro de Servicios y Gestión Empresarial, Servicio Nacional de Aprendizaje -SENA- Palmira (Colombia), and for any other institution with the same academic interests.